Determination of 8‐hydroxy‐2′‐ deoxyguanosine derivatized with 4‐chloro‐7‐ nitrobenzofurazan in urine by CE‐LIF. Issue 12 (13th April 2014) - Meng, Xiangying; Suo, Xingmei; Ding, Wenjun; Li, Xiangjun; Ding, Yongsheng; Lapizco‐Encinas, Blanca H.; Davalos, Rafael V.
<x xml:space="preserve">Abstract</x> Oxidative DNA damage is a common type of damage caused by reactive oxygen species (ROS) in the body, resulting in cell mutation and cell death. 8‐Hydroxy‐2′‐deoxyguanosine (8‐OHdG), one of the major products of oxidative DNA damage, is widely accepted as a biomarker for oxidative stress. However, it is challenging for the measurement of 8‐OHdG in biological samples because of the trace amount of 8‐OHdG and complex matrices. In this study, a simple and sensitive method was developed for the determination of 8‐OHdG in urine by using CE‐LIF and precapillary derivatization of 8‐OHdG with 4‐chloro‐7‐nitrobenzofurazan (NBD‐Cl). The conditions related to the derivatization were optimized step by step. Under the optimum conditions, the derivative showed the largest peak area and was successfully separated from the interfering substances in the urine samples. The method was validated according to a FDA guideline. The RSDs of the peak area and migration time of the analyte at three different levels were within 2.97–6.88% and 0.17–1.13%, respectively. Good linearity between the peak area and the concentration of the analyte added into the urine samples was obtained within a range of 5–150 nM (R2 > 0.99). The LOD of 3.0 nM was obtained based on a S/N of 3:1. The recoveries at three different levels were within 97.5–102.6%. The developed method was applied for the analysis of 8‐OHdG in seven urine samples in comparison to an ELISA method.